Premarital Pregnancy among Christian Adolescents: Lived Experiences, Social Stigma, and Pastoral Care - Bilsede Hukunala; Daniel Susanto (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2026)
Premarital pregnancy among Christian adolescents constitutes a complex social, psychological, and pastoral issue in Indonesia, where religious and cultural values strongly influence public perceptions of sexuality and family life. This study examines the causes and challenges of premarital pregnancy among church youth and evaluates the church's role in providing pastoral care. Using a qualitative multiple-case study design, data were collected through in-depth interviews and participant observation involving adolescent mothers, family members, and church leaders in two congregations of the Protestant Church of Maluku. The findings reveal that premarital pregnancy is associated with limited sexuality education, inadequate parent–child communication, and premarital sexual relationships. Adolescent mothers experience shame, stress, trauma, and social stigma, which are reinforced by socio-religious narratives that frame pregnancy outside marriage as sin and disgrace. The study further demonstrates that church responses remain largely reactive rather than restorative. It argues for holistic pastoral care integrating emotional support, parenting education, family accompaniment, and spiritual guidance to promote the well-being and social reintegration of adolescent mothers.